Aspects of Space - Marcus Kracht (Baltic International Yearbook of Cognition, Logic and Communication, 2015)
It is argued that spatial expressions come together with an encoding of the space called "aspect", which changes as we climb up the syntactic tree. The changing nature of aspect is necessary in order to simplify the meanings of elements. What appears to be a rather peculiar property of an element will be perfectly natural once we acknowledge that the elements compute on the space viewed in a particular way. Coordinates are always rooted in the landmark, for example. Thus, for the purpose of the distinction between static and dynamic it is not the "absolute" motion of the figure that counts, but the motion relative to the landmark.
Keywords: spatial expressions; model theoretic semantics; semantics; cognitive linguistics; cognition